A new species of Scirrotherium Edmund & Theodor, 1997 (Xenarthra, Cingulata, Pampatheriidae) from the late Miocene of South America - Gois Lima, Flavio (2013)
A new species of Scirrotherium Edmund & Theodor (Pampatheriidae) is described: S. carinatum. This genus was previously represented by a single species, S. hondaensis Edmund & Theodor, 1997, recorded from the middle Miocene (Laventan) of Colombia. Pampathere remains are common in the ‘Conglomerado osífero’ (late Miocene) of the Ituzaingó Formation in the Paraná River cliffs of Entre Ríos, Chubut (Argentina) and Acre (Brazil). All of them were referred to Kraglievichia paranense, and they are mostly osteoderms. However, only a few of these specimens are strictly consistent with that species. The new species described herein differs from S. hondaensis in having very thin osteoderms with more elaborate ornamentation. The movable band (or imbricate) osteoderms have a sculptured exposed surface and a single transverse row of anterior foramina; the lateral margins are wider and also bear foramina, and the longitudinal central elevation is long and proximally wide, and forms a posteriorly raised crest. This elevation is delimited by a fairly broad and shallow depression on each side, separating the marginal elevation from the longitudinal central one. The exposed surfaces of fixed (or fused) osteoderms bear large and deep anterior foramina, the longitudinal central elevation and delimiting depressions are very pronounced. This new species increases the known diversity of the pampatheres from the ‘Conglomerado osífero’. Additionally, a new nomenclatural scheme for Pampatheriidae osteoderms is proposed.